Rise and fall of civilization: causes from the perspective of the Qur'an - Ali, Mohd Mumtaz; Muhsin, Syed Muhammad (UTM Press and Faculty of Islamic Civilization, UTM., 2016)
The Qur'an contains voluminous portrayals about past civilizations with an imperative exploration to their causes of their rise and fall. The Qur'anic methodologies to survey the realities and events are grounded on ethical, empirical, spiritual, moral, universal and people-oriented appearances. Thus Qur'an analysis of past nations differs from the modern Western studies on features of earlier civilizations. From the Qur'anic perspective, the acceptance of True, Authentic and Universal Knowledge[revelation] is considered as the foundational factor for the realization of civilizational growth. Qur'an identifies and proves that human beings are the instrumental and decisive actors in the building of civilization or its destruction. The statements of the Qur'an underscore that whenever people established unethical attitude and denied spirituality in their life and committed immoral acts, they and their civilization tasted severe declination. This paper emphasizes that dissemination of "justice, unity and service for good" are three important moral concepts that have been mentioned in the Qur'an as integral to rise and fall of civilization.